2007
DOI: 10.1002/jnr.21537
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic acid stimulates the expression of myelin proteins in rat brain

Abstract: We have previously demonstrated that, in C6 glioma cells, eicosapentaenoic acid (EPA) stimulates the expression of proteolipid protein (PLP) via cAMP-mediated pathways. In this study, we investigated whether n-3 polyunsaturated fatty acids can affect myelinogenesis in vivo. A single dose of either EPA or docosahexaenoic acid (DHA) was injected intracerebroventricularly into 2-day-old rats, which were then killed after 3 days post-injection (p.i.). Total RNA was isolated from the medulla, cerebellum, and cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 31 publications
6
45
0
Order By: Relevance
“…Meta-analyses indicate that schizophrenia [27], bipolar disorder [28], and unipolar depression [29] are associated with PUFA deficits including DHA. Preclinical studies further suggest that n-3 PUFAs promote oligodendrocyte maturation and myelin expression [30,31], and are protective against axonal WM injury induced by trauma [32] and inflammation [33,34]. However, other studies suggest that maternal n-3 PUFA supplementation or deficiency impair neonatal axonal conduction, which is consistent with dysmyelination [35][36][37].…”
mentioning
confidence: 82%
“…Meta-analyses indicate that schizophrenia [27], bipolar disorder [28], and unipolar depression [29] are associated with PUFA deficits including DHA. Preclinical studies further suggest that n-3 PUFAs promote oligodendrocyte maturation and myelin expression [30,31], and are protective against axonal WM injury induced by trauma [32] and inflammation [33,34]. However, other studies suggest that maternal n-3 PUFA supplementation or deficiency impair neonatal axonal conduction, which is consistent with dysmyelination [35][36][37].…”
mentioning
confidence: 82%
“…For instance, DHA and its derivatives show anti-inflammatory (De Smedt-Peyrusse et al, 2008;Ló pez-Vales et al, 2010;Mullen et al, 2010), and neuroprotective attributes (Bazan, 2006(Bazan, ,2005Belayev et al, 2009). Moreover, DHA activates both Akt and CREB, which have been associated with neuroprotection and myelin stability in vitro and in vivo (Akbar et al, 2005;Mukherjee et al, 2004;Salvati et al, 2008;Wu et al, 2008). These beneficial effects have been reported in a number of neurological studies (Lauritzen et al, 2000;Lim et al, 2005;Pan et al, 2009;Rodriguez de Turco et al, 2002), including SCI (Huang et al, 2007;King et al, 2006;Lang-Lazdunski et al, 2003;Ward et al, 2010).…”
Section: Introductionmentioning
confidence: 90%
“…Akt and CREB have been associated with DHA protective effects on survival and myelin stability in vitro and in vivo (Akbar et al, 2005;Mukherjee et al, 2004;Salvati et al, 2008;Wu et al, 2008). We examined whether DHA pretreatment increases the mRNA and protein phosphorylation levels of Akt and CREB after acute SCI.…”
Section: Dha Pretreatment Induces the Upregulation And Activation Of mentioning
confidence: 99%
“…Another mechanism by which LC-PUFAs-especially ω-3 fatty acids-exert their function in the nervous system is their potential to regulate brain gene expression, as experimental studies conducted in recent years have shown [12,66,108]. LC-PUFAs are therefore a prime example of the close interaction between nutrients and genetic factors.…”
Section: Metabolism Of Pufas and Implications Of Metabolic Disordersmentioning
confidence: 99%